A High Volume, User-Friendly Immunization Clinic in Vellore, India: A Model for Urban Hospitals - Z Kompithra, Rajeev; R, Magdalenal; G Mathew, Leni; P Verghese, Valsan; Jacob John, T (Journal of Immunization, 2016)
The Expanded Program on Immunization (EPI) in India delivers vaccines under its policy, through government hospitals, health centers and outreach clinics. However, the national average full immunization coverage is stagnating at about 70%. The days and times of clinics are not always convenient for mothers working at home or employed outside. Moreover, vaccines not under EPI, but recommended by the Indian Academy of Pediatrics (IAP), are unavailable there, forcing mothers to go to private sector immunization clinics to get them. Recognizing the local need for user-friendly immunization clinic, we designed one in the Department of Child Health. The impetus came from local demand by a civil society organization (Rotary Club of Vellore). Our immunization clinic is open every working day (8.30 am to 4.00 pm) offering both groups of vaccines. Its success is illustrated by the fact that over 7000 children per month receive immunization in this clinic. We describe its design and operation so that this model may be replicated in other urban hospitals with pediatric sections.
Keywords: Immunization; Expanded Program on Immunization; Private sector Immunization Clinic; Non-EPI/newer Vaccines; Indian Academy of Pediatrics.